2017
DOI: 10.1002/ajhb.23069
|View full text |Cite
|
Sign up to set email alerts
|

The cost of reproduction in women: Reproductive effort and oxidative stress in premenopausal and postmenopausal American women

Abstract: We found no evidence of a trade-off between somatic maintenance as measured by 8-OHdG and reproductive effort in women from this American population. On the contrary, higher gravidity and parity in premenopausal women was associated with lower damage to cellular DNA caused by oxidative stress. These results highlight the importance of population variation and environmental conditions when testing the occurrence of life-history trade-offs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Polish women with four or more pregnancies had significantly elevated levels of a biomarker of DNA oxidative damage and of an antioxidative defence enzyme [54]. However, in women from the USA, no differences in oxidative damage were observed in relation to parity [55].…”
Section: Does Reproduction Have a Long-term Negative Impact? The Mechanisms Behind Reproductive Costs And Ageingmentioning
confidence: 99%
“…Polish women with four or more pregnancies had significantly elevated levels of a biomarker of DNA oxidative damage and of an antioxidative defence enzyme [54]. However, in women from the USA, no differences in oxidative damage were observed in relation to parity [55].…”
Section: Does Reproduction Have a Long-term Negative Impact? The Mechanisms Behind Reproductive Costs And Ageingmentioning
confidence: 99%
“…Across vertebrates, a number of studies also broadly support a trade-off between high fertility and reduced longevity [28,29]. Among female primates, including humans, results are inconsistent; some suggest that high fertility may be associated with negative health outcomes only in resource poor environments (reviewed in [27,30,3134]). All primates share unusually high parental investment and long lifespans [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous analyses of OS levels and reproductive investment in rural Polish women have shown significant associations between OS biomarkers and a composite measure of reproductive investment (Ziomkiewicz et al, 2016). However, follow-up research that broadened the ecological context of these studies with the investigation of urban American participants demonstrated no significant association between biomarkers of OS and reproductive investment for postmenopausal women (Ziomkiewicz et al, 2017). This revealed that ecological and lifestyle conditions that contribute to women's energetic status may contribute to variation in vulnerability to OS in association with reproductive effort (Jasienska, 2009).…”
Section: Oxidative Stress and Reproductionmentioning
confidence: 99%
“…Though the production of ROS is expected to increase as a result of the physiological changes associated with investment in reproduction, there is limited evidence about whether this alteration in the generation of ROS translates into an accumulated or long-lasting increase in OS levels, representing a potential lifetime cost of reproduction (Ziomkiewicz et al, 2016;Ziomkiewicz, Frumkin, Zhang, Sancilio, & Bribiescas, 2017). Some studies have suggested both that biomarkers of OS return to normal in the postpartum period, while others implied that these indicators remain elevated long after gestation is complete (Mutlu, Bas, Aksoy, & Taskin, 2012;Toescu et al, 2002).…”
Section: Oxidative Stress and Reproductionmentioning
confidence: 99%